Implementation of PBL Strategy in Strengthening Pancasila Student Profile in Independent Curriculum at SDI Darussalam Dungmas - Firda Zakiyatur Rofi’ah; Wulan Mardotun Nisak; Yogi Rismawindi Setia Mulya (Global Action and Education for Society, 2024)
Problem-Based Learning (PBL) strategy is one of the relevant student-centered learning approaches in integrating the values ​​of the Pancasila Student Profile into the learning process. At SDI Darussalam Dungmas, this strategy has been applied in learning the Al-Qur'an Hadith as an effort to improve the profile of Pancasila students. This study aims to describe the implementation of the Problem-Based Learning (PBL) learning strategy in strengthening the values ​​of the Pancasila Student Profile at SDI Darussalam Dungmas. The study used a descriptive qualitative method, data were collected through observations of learning activities and interviews with religious teachers. The results showed that the application of the Problem-Based Learning (PBL) strategy in learning the Al-Qur'an Hadith, especially the hadith material about piety, succeeded in activating active student involvement in the learning process. Through the stages of PBL, starting from problem identification, group discussions, to presentations and evaluations, students are encouraged to develop critical thinking skills and understand religious values ​​in depth. In addition, PBL activities also foster an attitude of mutual cooperation, independence, and the practice of piety values ​​in everyday life. Thus, the PBL strategy implemented at SDI Darussalam Dungmas is able to build student character according to the profile of Pancasila students. Therefore, it is suggested that the PBL strategy can be applied more widely, especially at the elementary education level as a means to strengthen the profile of Pancasila students.